PENGARUH FEMINISME TERHADAP KEBIJAKAN LUAR NEGERI ISLANDIA (2008-2013) - Sugesti, Gebi Purnama; ", Pazli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study will analyze the influence of feminism in Iceland’s foreign policy year 2008-2013. Feminism have influenced social and political life in Iceland, especially in gender equality. Gender equality is one of the Iceland’s government’s key emphases and it’s an important aspect of Iceland’s international work on human rights.This research will show that how external aspects can also affect in Iceland’s foreign policy. Especially in increase gender equality and women’s empowerment. There is five aspects that Iceland’s concerns are, like politic, economy, education, health, and security. These are including support some specific projects, funds and organisations. Feminism perspective, gender concept and foreign policy decision making theory are used to discuss this research.As for the method used in the study is qualitative research methods with explanation analysis methods. Data collection techniques are used library research techniques which utilizes secondary data obtaine d through library were abstracted from the literature such as books, journals, reports, documents and other materials that support this research.Feminism has give significant influence in Iceland’s foreign policy. Iceland has adopted The United Nations Security Council Resolution 1325 (2000) on women, peace and security through their Plan of Action and also Iceland has built Strategy for Iceland’s Development Cooperation 2011-2014 acording to United Nations Millenium Development Goals (MDG). Both of the strategies give strong impact for the implementations of Iceland’s Foreign Policy.Key Word: Influence, Feminism, Iceland, Foreign Policy, Gender Equality